Pollution prevention reducing waste in the workplace - Grulich, Madeline M; Coastal Video Communications (Virginia : Coastal Video Communications, 1990)
Pollution prevention is one of yourcompany's most critical responsibilities. It can generate positive public relations. It can result in savings. And it will help protect your community's health and environment
Keywords: Source reduction (Waste management); Waste minimization; Pollution